Helminth Fauna of Two Species of Physalaemus (Anura: Leiuperidae) from an Undisturbed Fragment of the Atlantic Rainforest, Southeastern Brazil - Toledo, Gislayne M. [UNESP]; Aguiar, Aline [UNESP]; Silva, Reinaldo J. [UNESP]; Anjos, Luciano A. [UNESP] (Amer Soc Parasitologists, 2013)
Two amphibian species, Physalaemus cuvieri and Physalaemus olfersii, from Serra do Mar State Park, which is an old-growth environment of the Atlantic Rainforest in southeastern Brazil, were surveyed for endoparasites. Hosts were sampled in 2 ponds; each was colonized by only 1 Physalaemus species. The overall prevalence of helminths was high and similar in both amphibian species. The mean intensity of infection in P. olfersii did not differ statistically from that in P. cuvieri. Nine helminth species were found: 2 acanthocephalans, 1 cestode, and 6 nematodes. Parasite richness in the 2 host species was similar. The composition of helminth fauna differed but the 2 hosts shared the most prevalent taxon of nematode (an unidentified species of Cosmocercidae). All helminth species exhibited an aggregated distribution pattern in the host species. The present results demonstrate relatively low species richness and the dominance of generalist parasite species. This study contributes to knowledge regarding the structure and composition of the helminth community in anurans.